Pengaruh Kinerja dan Kualitas Pelayanan Terhadap Loyalitas Pasien pada Puskesmas di Kota Bima - Imamah, Imamah; Ardana Putra, I Nyoman Nugraha; Sardjijo, Sardjijo (Universitas Hamzanwadi, 2024)
This research aims to analyze the influence of service performance and quality of health services on patient loyalty at Community Health Centers in Bima City. The sample for this study was patients or families of patients who visited community health centers to receive health services at community health centers in the Bima City area, namely: East Rasana'E Health Center, Penana'E Health Center, Mpunda Health Center, Asakota Health Center, and Paruga Na'E Community Health Center totaling 250 person. The research instrument used a questionnaire with a Likert scale. The data analysis technique uses multiple linear regression. The research conclusion is that the performance of community health centers has a positive and significant effect on patient loyalty to visit and use medicines according to instructions from nurses/doctors at all community health centers in Bima City. The quality of Puskesmas services in Bima City has a positive and significant effect on patient loyalty to visit and take medicine according to instructions from nurses/doctors at all Puskesmas in Bima City